2023
DOI: 10.1108/ijrdm-07-2022-0265
|View full text |Cite
|
Sign up to set email alerts
|

The online flow and its influence on awe experience: an AI-enabled e-tail service exploration

Abstract: PurposeThe study applied the stimulus–organism–response (S–O–R) framework to investigate the influence of flow elements (e.g. perceived control, concentration and cognitive enjoyment) on artificial intelligence (AI)-enabled e-tail services in evoking awe experience in online fashion apparel context.Design/methodology/approachData of 739 active users of online fashion retail shoppers were collected using Amazon Mechanical Turk (MTurk). Partial least square-structural equation modeling was used for analysis.Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…In fact, emotional attachment mediates the customer experience and repurchase intention and e-WoM, and thus the promotional strategy should focus on communicating emotional attachment with a portray of fashion apps shoppers. Further, this may be promising starting point for digital interface designers to integrate themes that general emotional state which are physiological, behavioral and self-induced (Khare et al, 2023).…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, emotional attachment mediates the customer experience and repurchase intention and e-WoM, and thus the promotional strategy should focus on communicating emotional attachment with a portray of fashion apps shoppers. Further, this may be promising starting point for digital interface designers to integrate themes that general emotional state which are physiological, behavioral and self-induced (Khare et al, 2023).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Although previous research has demonstrated the notable influence of e-servicescape on consumer behavior in online settings (Lai et al, 2014;Tran et al, 2012;Wu et al, 2017;Tran and Strutton, 2020), limited attention has been given to its role in shaping consumer behavior within fashion apps. A well-structured and user-friendly e-servicescape can elicit favorable emotions in customers, leading to increased engagement, loyalty and favorable word-of-mouth endorsements (Saputra, 2021;Kautish and Khare, 2022;Khare et al, 2023). Therefore, this study will go further by considering the impact of the e-servicescape of fashion apps on users' emotional attachment with the apps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation